Social media uptake in Cyprus - Or is it just a new fad? - Melanthiou, Yioula; Papasolomou, Ioanna; Komodromos, Marcos (My University, 2015)
This article responds to the lack of research on the adoption and practice of social media by companies, by focusing on the findings of a study carried out in the business sector in Cyprus. The study objectives were to identify if and how companies in Cyprus use social media, how effective they perceive it to be, and what specific factors affect social media adoption. Through structured interviews, an empirical investigation within the SME sector in Cyprus showed that local businesspeople are reluctant to adopt social media and incorporate it in their promotional mix.
Keywords: technology marketing; Cyprus; social media adoption; branding; business sector; SMEs; small and medium-sized enterprises